2010
DOI: 10.4161/auto.6.1.10700
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in nuclear receptor PPARγ-deficient mouse prostatic carcinogenesis

Abstract: Peroxisome proliferator-activated receptor-gamma (PPARgamma) is a major modulator of cellular lipid metabolism and organelle differentiation. To understand whether autophagy is involved in the processes of dysregulated fatty acid oxidation and induced oxidative stress accompanying prostatic carcinogenesis, we characterized in vitro and in vivo models of PPARgamma- and PPARgamma2-deficiency in mouse prostate epithelia. Autophagy accompanied the altered cellular proliferation and de-differentiation that resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…(Fig. s3A and B) (13, 14). These data suggest that the crosstalk between macrophages and prostate epithelial cells was able to enhance STAT3 activation in prostate epithelial cells, regardless of whether the macrophages originated from an established cell line or murine bone marrow.…”
Section: Resultsmentioning
confidence: 99%
“…(Fig. s3A and B) (13, 14). These data suggest that the crosstalk between macrophages and prostate epithelial cells was able to enhance STAT3 activation in prostate epithelial cells, regardless of whether the macrophages originated from an established cell line or murine bone marrow.…”
Section: Resultsmentioning
confidence: 99%
“…A link between IBD and lysosomal alterations have been suggested earlier [16]. More recently, disruption of PPAR γ in mice resulted in focal hyperplasia, accumulation of lysosomes and dysregulation of pathways related to lysosomal maturation in a prostatic cancer model [17], [18]. Cathepsins are lysosomal acid hydrolases whose transcription is enhanced in colonic mucosa in response to dietary DSS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that enhanced autophagy may function as a tumor suppressing mechanism, and defects in autophagy can promote cancer (15). The mechanisms of autophagic cell death can be used as an effective method for cancer prevention and treatment (16).…”
Section: Human Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%